2014
DOI: 10.1590/abd1806-4841.20143020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mucocutaneous candidiasis: a case with exuberant cutaneous horns in nipples

Abstract: Chronic mucocutaneous candidiasis is a rare disorder characterized by persistent and recurrent infections by Candida due to changes in cellular immunity and may be associated with autoimmune endocrine disorders. It is refractory to the usual antifungal treatments, which merely control it with imidazole derivatives. This reports the case of a 50-year-old female patient who referred vaginal discharge associated with vulvar ulcerated lesions and whitish plaques on oral and genital mucous membranes of onset in ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
1
10
0
1
Order By: Relevance
“…The most common Newton classification of CAC is type II, which corresponds to an area of diffuse erythema on the palate (Newton, 1962;Chambo-Filho et al, 2014), consistent with the higher prevalence of type II lesions observed in the present study. This distribution most likely occurs because patients with CAC often wear complete dentures, which entails a larger surface area of contact between the prosthesis and palate.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The most common Newton classification of CAC is type II, which corresponds to an area of diffuse erythema on the palate (Newton, 1962;Chambo-Filho et al, 2014), consistent with the higher prevalence of type II lesions observed in the present study. This distribution most likely occurs because patients with CAC often wear complete dentures, which entails a larger surface area of contact between the prosthesis and palate.…”
Section: Discussionsupporting
confidence: 89%
“…Among the several clinical forms of candidiasis, CAC is considered one of the most ubiquitous of all opportunistic infections, frequently co-occurring with angular cheilitis, at the labial commissures, or in the "kissing lesion" of the dorsum of the tongue (Rao, 2012;Chambo-Filho et al, 2014;Brandolt et al, 2017;Hellstein & Marek, 2019). Studies suggest that women are more affected than men; however, it is known that women are more likely to seek medical attention and that incidence increases with advancing age, i.e., older adults have a higher prevalence of this condition, particularly due to denture use and difficulties in oral hygiene (Rao, 2012;Chambo-Filho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To cause invasive infections, some pathogenic fungi transition between yeast and filament forms, while others cause infections as single morphotypes (1)(2)(3)(4)(5)(6)(7). Candida albicans is unusual among fungal pathogens in that it grows in both yeast and filamentous forms during infection of humans, mice, zebrafish, and invertebrate hosts (8)(9)(10)(11)(12)(13)(14)(15). While both forms contribute to virulence, it is still unclear how this differentiation between shapes drives specific aspects of pathogenesis.…”
mentioning
confidence: 99%
“…Chambô Filho ve ark. (17) meme başın-da deri boynuzu şeklinde ortaya çıkan bir kronik mukokütanöz kandidoz olgusunu rapor etmişler-dir. Vaskülitli bir hastada ise Candida albicans'a bağlı penil miçetoma, ilk kez bildirilmiştir (18) .…”
Section: Kli̇ni̇k Bulgularunclassified